Human Pulpal Responses to Peroxides - De Oliveira Ribeiro, Rafael Antonio [UNESP]; Soares, Igor Paulino Mendes [UNESP]; Soares, Diana Gabriela; Briso, André Luiz Fraga [UNESP]; Hebling, Josimeri [UNESP]; De Souza Costa, Carlos Alberto [UNESP] (Springer Nature, 2023)
Most patients subjected to professional tooth bleaching report posttreatment hypersensitivity that varies from slight to intolerable. The pathway for bleaching-induced tooth sensitivity is associated with the capability of the main active component of bleaching gels, hydrogen peroxide (H2O2), to diffuse through enamel and dentin to reach the pulp tissue. Since H2O2 is a reactive oxygen species (ROS) with intense oxidative potential, the contact of this molecule with the pulp tissue promotes oxidative cell damage, leading to local connective inflammation that triggers nociceptive stimulus. However, as this clinical symptom is transient, it is still unclear how relevant this adverse effect is to the pulp-dentin complex. Thus, in this chapter, the authors describe relevant clinical and laboratory data currently provided by several in vitro and in vivo studies evaluating traditional in-office (professional) and at-home bleaching therapies and discuss alternative tooth bleaching protocols that may prevent or at least minimize the harmful effects of these oxidative esthetic treatments to the pulp tissue vitality.